The large MIS 4 and long MIS 2 glacier maxima on the southern tip of South America - Peltier, Carly; Kaplan, Michael R.; Birkel, Sean D.; Soteres, Rodrigo L.; Sagredo, Esteban A.; Aravena Donaire, Juan Carlos; Araos, Jose; Moreno, Patricio; Schwartz, Roseanne; Schaefer, Joerg M. (My University, 2021)
Robust glacial chronologies are needed to address the fundamental questions of when and why Ice Age climates begin and end. Well-preserved glacial deposits left by large ice sheet lobes adjacent to Estrecho de Magallanes (53 degrees S; Chile) in southernmost South America provide a unique opportunity to reconstruct the timing and fine structure of the last two major glaciations, as well as the last termination. We present a new precise Be-10 surface exposure dataset of 34 moraine boulders directly tied to a recently published, high resolution glacial geomorphic map of the deposits left by the Magallanes lobe. We find that the southern section of the Patagonian Ice Sheet was more extensive during Marine Isotope Stage 4 (MIS 4) than during MIS 2, representing the first direct dating of the MIS 4 glacier culmination in South America. Similar to the MIS 2 glacial maxima, within MIS 4 there were multiple advances that we date (n = 6 samples) to between 67.5 +/- 2.1 and 62.1 +/- 2.0 ka. A similarly timed MIS 4 advance was identified in New Zealand, indicating that this is a hemisphere-wide glacier-climate signal, which is further corroborated by South Atlantic and Pacific temperature proxy records. Inboard of the MIS 4 moraine complex, we date a sequence of geomorphically distinct MIS 2 moraines that represent separate major periods of glacial stability. The MIS 2 maximum extent occurred by 27.4 +/- 0.8 ka (n = 4; arithmetic mean, with the standard error of the mean and 3% propagated production rate error) and was followed by at least four more full glacial culminations at 25.7 +/- 0.8 (n = 3), 23.9 +/- 0.8 (n = 5), 19.1 +/- 0.7 (n = 3), and 18.1 +/- 0.6 ka (n = 3), which represent periods when the glacier was in equilibrium with the climate for long enough to form major moraines. About 18 km inboard, this sequence is followed by smaller-scale recessional moraine crests, deposited on drumlinized terrain rather than a moraine drift, that we date to 18.0 +/- 0.8 ka, indicating the glacier was in net retreat at this time. Tentative results from a 2D ice sheet model suggest that the Magallanes lobe may have reached mapped inner and outer MIS 2 moraines from a climate with approximately 4.5 degrees C and 5.5 degrees C cooler summers, respectively, assuming similar to 25% less annual precipitation, relative to modern climate. We hypothesize that during the last glacial cycle, shifts in the subtropical and subantarctic fronts, and related ocean-atmosphere patterns, explain MIS 4 to 2 glacial behavior in the southern mid-latitudes. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: pleistocene; glaciation; paleoclimatology; south america; patagonia; paleo ice sheet modeling; mis 4; mis 2; glacial geomorphology; 10be exposure dating